MILLED CASSAVA PRODUCTION CAPACITY MODEL THROUGH MACHINE EFFECTIVENESS ANALYSIS - Santosa, Sesar Husen (Journal of Industrial Engineering Management, 2024)
The very high demand for the tapioca flour industry causes good quality and quantity tapioca flour. This condition causes the tapioca flour SMIs have to manage production activities to meet the needs of the industry. The flour production process cannot be separated from the cassava milling machine effectiveness. Based on the results of the milling machine analysis for one year, the availability = 65,16%, performance = 53.62%, Quality Rate = 89.60% and OEE = 31.88%. Based on the OEE value and the amount of production, the regression equation model is obtained, namely ground cassava (Kg) = 5155 + 11037 OEE with Determination value (R2) = 94,8 %. This regression model is used as the basis for determining the ideal production capacity of ground cassava in SMIs. According to Seiichi Nakajima's standard ideal OEE, which is 85%, the ideal production capacity of ground cassava in SMIs is 14,536 kg/month based on the regression model.